PENINGKATAN HASIL BELAJAR SISWA PADA MATERI GEOMETRI DENGAN MENGGUNAKAN MEDIA GAMBAR DI KELAS II SD INPRES PALUPI - Sevtin Sri Indra Ponamon; Herlina; Renawati (LPPM Universitas Cipta Mandiri, 2025)
Problems identified by teachers during the learning process in class II of SD Inpres Palupi. Students show a low level of activity in the learning process, which can be attributed to the lack of learning facilities available in the classroom, such as textbooks, as well as limitations in the use of teaching aids or learning media by teachers. In the implementation of the teaching and learning process in Class II of SD Inpres Palupi, there are indications that most of the students show a low level of activity. This is due to the lack of use of media, including visual media, which has implications for students' lack of understanding of the explanations given by the teacher). This study focused on grade 2 students of SD Inpres Palupi, with a total of 28 participants from SD Inpres Palupi. The results obtained showed that at the average level of pre-action, cycle 1 had an increase of 9.09%, while from cycle 1 to cycle 2 there was an increase of 36.36%. This shows an increase in the use of the picture method in the teaching of mathematics.